Falun Dafa truthfulness, compassion, forbearance. ([China] Falun Dafa, 2002)
Falun Dafa or Falun Gong is a holistic cultivation system that is based on the characteristics of the universe: truthfulness, compassion and forbearance. It is a popular qigong activity and does not have any particular organizational structure, nor any political objective.
1. Falun Dafa exercise demo (3 min.) -- 2. A peaceful journey of Falun Dafa ( 31 min.) -- 3. Doubts of Tiananmen self-immolations (20 min.) -- 4. Human rights violation (an appeal to China) (14 min.)
Title on container: Falun Dafa : truthfulness, compassion, tolerance.
Keywords: Falun Gong (Organization).; Human rights; China -- Politics and government